New Detailed Modeling of GICs in the Spanish Power Transmission Grid - J. M. Torta; S. Marsal; J. Ledo; P. Queralt; V. Canillas‐Pérez; P. Piña‐Varas; J. J. Curto; A. Marcuello; A. Martí (Space Weather)
Abstract The threat of Geomagnetically Induced Currents (GICs) driven by severe Space Weather looms over technological systems such as power grids. Assessing their vulnerability is thus vital to avoid damages or even disruption of the electrical power supply. This endeavor, however, entails an interdisciplinary approach, ranging from the characterization of the geoelectrical structure of the Earth beneath and around the area of interest, or the modeling of the power network from its parameters and topology, and including the validation of the modeling process by means of (direct or indirect) GIC flow measurements. In this paper, we summarize our current achievements focused on mainland Spain, concentrating on the improvements reached after going from a homogeneous Earth's resistivity to an alternative 3D electrical resistivity distribution approach to geoelectric field computation, which is still in progress because new empirical impedance tensors are needed, mainly at sites in the west of the Iberian Peninsula. The second major achievement has come from the addition of the 220 kV level to the network model. The overall improvement has been validated against real GIC data in one area of the country. The new vulnerability maps show that in some nodes the predicted GIC has been substantially reduced by the sum of both effects. The assessment has been carried out down to the level of the individual windings of each transformer, and examples of the estimated GIC flow are given for substations with numerous power transmission lines converging to them at diverse orientations.